2009
DOI: 10.1002/anie.200900513
|View full text |Cite
|
Sign up to set email alerts
|

Primary Peptide Folding Dynamics Observed with Ultrafast Temperature Jump

Abstract: The folding dynamics of proteins and polypeptides is a complex process involving different time and length scales. [1][2][3][4] Among the secondary structural elements the α-helix is the most commonly found configuration with its stability resulting from the unique hydrogen bonding; the C=O group of an amino acid at the position i forms a hydrogen bond with the N-H group of another amino acid located at the position i+4. The thermodynamic properties of the α-helix are understood in the context of the helix-coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 34 publications
6
60
2
Order By: Relevance
“…Indeed, helix folding experiments demonstrated that the timescale of the nucleation step could be relatively fast: α-helix nucleation, when observed under no-zipping conditions, occurs on a few-nanosecond timescale, which is consistent with analytical and computational assessments carried out in this (8,9) and other laboratories (28,29). In contrast, the overall helix folding timescale at room temperature is broadly distributed depending on sequence, typically being hundreds of nanoseconds (18,19).…”
Section: Kinetic Zipper Modelsupporting
confidence: 80%
See 1 more Smart Citation
“…Indeed, helix folding experiments demonstrated that the timescale of the nucleation step could be relatively fast: α-helix nucleation, when observed under no-zipping conditions, occurs on a few-nanosecond timescale, which is consistent with analytical and computational assessments carried out in this (8,9) and other laboratories (28,29). In contrast, the overall helix folding timescale at room temperature is broadly distributed depending on sequence, typically being hundreds of nanoseconds (18,19).…”
Section: Kinetic Zipper Modelsupporting
confidence: 80%
“…Thus, relatively little was known about the associated kinetics until the end of the 1990s (3). With the advent of temperature-jump (T-jump) experimental techniques, the rates of the helix−coil transitions became readily measurable (4-6), whereas the progress in temporal resolution spanning both the nanosecond (7) and picosecond (8) regimes elucidated the early steps of folding/unfolding. Importantly, studies of the elementary steps accompanying such processes can now uncover the nature of kinetic-intermediate states, as well as their characteristic lifetimes (8,9).…”
mentioning
confidence: 99%
“…Thus, a conformational change is required to mobilize the proton from the N-terminus to the C-terminal amide nitrogen. It is known that globule-helix conformational transitions of peptides are rapid [38,39]. Seemingly at odds with our conclusion, experimental and molecular dynamics (MD) studies have suggested that no helical structures should be expected from protonated Ala 15 H + [40].…”
Section: Resultscontrasting
confidence: 53%
“…We note that the rise of the expansion is within the T-jump resolution. This rise simply reflects the time for heat transfer from the dye to the protein and it is typically on a subnanosecond timescale (16). Here, it is of no relevance.…”
Section: Significancementioning
confidence: 99%